Efficient and Selective CO2 Reduction to Formate on Pd‐Doped Pb3(CO3)2(OH)2: Dynamic Catalyst Reconstruction and Accelerated CO2 Protonation. Issue 16 (9th March 2022) - Huang, Wenjing; Wang, Yijin; Liu, Jiawei; Wang, Yu; Liu, Daobin; Dong, Jingfeng; Jia, Ning; Yang, Lan; Liu, Chuntai; Liu, Zheng; Liu, Bin; Yan, Qingyu
Abstract: Exploring catalyst reconstruction under the electrochemical condition is critical to understanding the catalyst structure–activity relationship as well as to design effective electrocatalysts. Herein, a PbF2 nanocluster is synthesized and its self‐reconstruction under the CO2 reduction condition is investigated. F − leaching, CO2 ‐saturated environment, and application of a cathodic potential induce self‐reconstruction of PbF2 to Pb3 (CO3 )2 (OH)2, which effectively catalyze the CO2 reduction to formate. The in situ formed Pb3 (CO3 )2 (OH)2 discloses >80% formate Faradaic efficiencies (FEs) across a broad range of potentials and achieves a maximum formate FE of ≈90.1% at −1.2 V versus reversible hydrogen electrode (RHE). Kinetic studies show that the CO2 reduction reaction (CO2 RR) on the Pb3 (CO3 )2 (OH)2 is rate‐limited at the CO2 protonation step, in which proton is supplied by bicarbonate (HCO3 − ) in the electrolyte. To improve the CO2 RR kinetics, the Pb3 (CO3 )2 (OH)2 is further doped with Pd (4 wt%) to enhance its HCO3 − adsorption, which leads to accelerated protonation of CO2 . Therefore, the Pd‐Pb3 (CO3 )2 (OH)2 (4 wt%) reveals higher formate FEs of >90% from −0.8 to −1.2 V versus RHE and reaches a maximum formate FE of 96.5% at −1.2 V versus RHE with a current density of ≈13 mA cm −2 . Abstract : This paper introduces pre‐synthesized PbF2 nanoclusters in situ self‐reconstructed into active Pb3 (CO3 )2 (OH)2 during the CO2 reduction process. To improve the CO2 reduction reaction kinetics, Pb3 (CO3 )2 (OH)2 is further doped with Pd (4 wt%), which leads to accelerated protonation of CO2 . Therefore, the Pd‐Pb3 (CO3 )2 (OH)2 (4 wt%) yields brilliant electrochemical performance toward CO2 ‐to‐formate.